Chinese haze versus Western smog: lessons learned - Zhang, Junfeng (Jim); Samet, Jonathan M. (Journal of Thoracic Disease; Vol 7, No 1 (January 26, 2015): Journal of Thoracic Disease (Haze, Health and Disease), 2014)
Air pollution in many Chinese cities has been so severe in recent years that a special terminology, the “Chinese haze”, was created to describe China’s air quality problem. Historically, the problem of Chinese haze has developed several decades after Western high-income countries have significantly improved their air quality from the smog-laden days in the early- and mid-20th century. Hence it is important to provide a global and historical perspective to help China combat the current air pollution problems. In this regard, this article addresses the followings specific questions: (I) What is the Chinese haze in comparison with the sulfurous (London-type) smog and the photochemical (Los Angeles-type) smog? (II) How does Chinese haze fit into the current trend of global air pollution transition? (III) What are the major mitigation measures that have improved air quality in Western countries? and (IV) What specific recommendations for China can be derived from lessons and experiences from Western countries?